2017
DOI: 10.1515/biol-2017-0028
|View full text |Cite
|
Sign up to set email alerts
|

Tudor-SN protein expression in colorectal cancer and its association with clinical characteristics

Abstract: ObjectivesTudor-SN protein (SND1) is known to be up-regulated in some types of human malignancies and functions as an oncogene. The objective of our study was to investigate the expression and prognostic value of SND1 in human colorectal cancer (CRC).MethodsReal-time PCR and western blot were performed to examine the SND1 expression in human CRC and their corresponding non-cancerous colon tissues from 42 patients. Its clinical significance was evaluated by analyzing its expression with multiple pathological ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…-High expression in invasive/metastatic breast cancer cell lines compared to poor cancer lines (Zhu & Tan, 2017;Xing et al, 2018).…”
Section: Staphylococcal Nuclease Domaincontaining Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…-High expression in invasive/metastatic breast cancer cell lines compared to poor cancer lines (Zhu & Tan, 2017;Xing et al, 2018).…”
Section: Staphylococcal Nuclease Domaincontaining Proteinmentioning
confidence: 99%
“…This is probably due to its role in stimulating transcription, mRNA splicing, and silencing. Other studies indicated that TSN would be acceptable for novel diagnostics and prognoses of colorectal cancer (Zhu & Tan, 2017) and lung cancer (Xing et al, 2018). The functional activation of TSN would be a novel mechanism causing the early carcinogenesis of cancer, which may be used to predict survival in cancer patients.…”
Section: Staphylococcal Nuclease Domain-containing Protein (Low Score...mentioning
confidence: 99%